The Impact of Teacher-Student Relationships on Learning Engagement: A Study of Guangxi Universities in China - Shuangyuan, Lan; Vijayaratnam, Phawani; Wei , Huang (Journal of Ecohumanism, 2024)
The study aims to examine the significant relationship between teacher-student relationship and students' learning engagement in China Guangxi Universities. Data was collected using an online Likert 5 scaling questionnaire distributed to students in three Guangxi Universities. The Pearson Correlation analysis and multiple regression results confirmed the positive impact of teacher-student interaction, learning motivation, and perceived teacher support on student engagement. According to the regression analysis, Perceived Teachers’ Support has the strongest impact on Chinese Students Learning Engagement in China Guangxi Universities. This study fills the gap of lack of research on teacher-student relationship and students’ learning engagement based on the subjective model. The practical recommendations will be proposed based on the findings to improve the quality of education